2011
DOI: 10.1007/s11101-011-9211-7
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone synthase and its functions in plant resistance

Abstract: Chalcone synthase (CHS, EC 2.3.1.74) is a key enzyme of the flavonoid/isoflavonoid biosynthesis pathway. Besides being part of the plant developmental program the CHS gene expression is induced in plants under stress conditions such as UV light, bacterial or fungal infection. CHS expression causes accumulation of flavonoid and isoflavonoid phytoalexins and is involved in the salicylic acid defense pathway. This review will discuss CHS and its function in plant resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
358
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(394 citation statements)
references
References 157 publications
16
358
0
3
Order By: Relevance
“…19 Our study also identified it as having a significantly enhanced expression in the leaves. Another protein, the GHSdependent dehydroascorbate reductase 1 (gi:6939839) also showed an increase in expression.…”
Section: Metabolismsupporting
confidence: 57%
“…19 Our study also identified it as having a significantly enhanced expression in the leaves. Another protein, the GHSdependent dehydroascorbate reductase 1 (gi:6939839) also showed an increase in expression.…”
Section: Metabolismsupporting
confidence: 57%
“…In Arabidopsis, it has been shown that mutants deficient in phenylpropanoid compounds were considerably more susceptible to UV-B radiation than corresponding wild-type lines (Hectors et al, 2012). Furthermore, studies on parsley (Petroselinum crispum) cell cultures have shown that UV light is responsible for the induction of CHS expression by the de novo synthesis of the active enzyme (Dao et al, 2011). The herbivory or wounding induces metabolic changes that involve discerning the modulation of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CHS genes can be induced by various biotic and abiotic elicitations, including light/UV light, phytopathogens, mechanical wounding, and plant hormones (Dao et al, 2011). These modulate gene expression by interacting with the cis-regulatory elements in the promoter regions.…”
Section: Isolation and In Silico Characterization Of Rechs Promoter Smentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of phytoalexins, activation of pathogenesis-related proteins and modification of plant hormone balance are often observed (Bonasera et al 2006;Dugé de Bernonville et al 2012; Van der Zwet et al 2012). Following E. amylovora infection, in apple tree tissues, significant changes in secondary metabolite profiles, especially in the phenolic compounds pool are detected (Dao et al 2011). These compounds, which generally fall into two categories i.e.…”
Section: Introductionmentioning
confidence: 99%